Knowledge, Attitude, and Preventive Practices among Prison Inmates in Ogbomoso Prison at Oyo State, South West Nigeria - Saliu, Abdulsalam; Akintunde, Babatunde (International Journal of Reproductive Medicine, 2014)
Prisoners are at special risk for infection with human immunodeficiency virus (HIV) because of overcrowded prisons, unprotected sex and sexual assault, occurrence of sexual practices that are risky to health, unsafe injecting practices, and inadequate HIV prevention, care, and support services. This study aimed to describe the knowledge, attitude, and preventive practices towards HIV/AIDS by male inmates in Ogbomoso Prison at Oyo State, South West Nigeria. This was a cross-sectional study. A simple random sampling method was employed to select 167 male participants and data were collected using pretested structured interviewer-administered questionnaire. The data were collated and analyzed using the Statistical Package for Social Sciences version 17. Fifty (29.9%) were in the age group 20–24 years with mean age of 30.99±11.41. About half (50.3%) had been married before incarceration. Family and friends (30%), health care workers (25%), prison staff (20%), and mass media (25%) were the commonest sources of information on HIV/AIDS. Knowledge about HIV was found to be high (94.6%). About 68.9% believed that people with the disease should be avoided. The knowledge about HIV/AIDS among inmates was high, but misconceptions about HIV/AIDS are still rife among the prisoners and educational programs would be required to correct this.